Fundamental conceptions underlying areas of jurisprudence and how they shape related rulings: a comparative study with special reference to partnership - Sadique, Muhammad Abdurrahman (2012)
In studying Islamic law, it becomes evident that in many areas, the relevant rulings are linked together by a fundamental conception that acts as the foundation for all the related rulings. These fundamental conceptions dictate the structural framework of the relevant area, providing shape to the rulings governing diverse issues. These underlying theories are often not referred to explicitly in the works of Islamic law, which generally suffice with explaining the relevant rules.